ANALISIS DATA PANEL MIGRASI MASUK RISEN DI PULAU JAWA DAN SUMATERA PERIODE 1995-2015 - Dio Dwi Saputra; Winih Budiarti (Jurnal Kependudukan Indonesia, 2017)
Migration could be one of the causes of inequality in population distribution in Indonesia. Based on data from the 2010 Population Census, provinces in Java and Sumatera became the primary destination for recent migrants. In the meantime, these two islands have already become the highest population density islands in Indonesia. This situation could result in the broader gap of interregional population distribution. By using population census and intercensal survey data, this paper aims to analyze the general description of recent migrants in 16 provinces in Java and Sumatera islands during five periods, i.e., 1995, 2000, 2005, 2010, and 2015. This study also identifies pull factors which influenced the in-migrants flow to these provinces. In general, the concentration of recent in-migrants in Java islands in 1995 started to change toward Riau and Riau Island Province in the 2000s. Moreover, regression analysis of panel data showed that the share of the industrial sector and unemployment rate have a significant effect on the number of recent migrants in provinces in Java and Sumatera.